A comparison of two types of electrospun chitosan membranes and a collagen membrane in vivo. Issue 1 (January 2021) - Su, Hengjie; Fujiwara, Tomoko; Anderson, Kenneth M.; Karydis, Anastasios; Ghadri, M. Najib; Bumgardner, Joel D.
Abstract: Background: Electrospun chitosan membranes subjected to post-spinning processes using either triethylamine/ tert -butyloxycarbonyl (TEA/tBOC) or butyryl-anhydride (BA) modifications to maintain nanofiber structure have exhibited potential for use in guided bone regeneration applications. The aim of this study was to evaluate ability of the modified membranes to support healing of bone-grafted defects as compared to a commercial collagen membrane. Method: TEA/tBOC-treated and BA-treated chitosan membranes were characterized for fiber morphology by electron microscopy, residual trifluoroacetic acid by 19 F NMR and endotoxin level using an endotoxin quantitation kit (ThermoScientific, US). Chitosan membranes were cut into 12 mm diameter disks. An 8 mm calvarial defect was created in each of 48 male rats and then filled with Bio-Oss (Geistlich, US) bone graft. The grafted defects were covered with either (1) TEA/tBOC-treated chitosan membrane (2) BA-treated chitosan membrane or (3) the control BioMend Extend (Zimmer Biomet, US) collagen membrane. After 3 and 8 weeks, the rats were euthanized and calvaria was retrieved for microCT and histological analyses (n = 8/group/time points). Results: Both TEA/tBOC-treated and BA-treated membranes were composed of nanofibers in the ∼231 to ∼284 nm range respectively, exhibited no TFA salt residue and low endotoxin levels (≤0.1 ± 0.01 EU/membrane). All membranes supported increased bone growth from 3 weeks to 8 weeks though there was no significant difference among the membrane types. However, TEA/tBOC treated and BA treated chitosan membranes both showed significantly greater bone density (∼6% greater at 3 weeks and ∼8% greater at 8 weeks) as compared to BioMend Extend collagen membrane at both time points (p = 0.0002). Conclusions: Chitosan membranes supported better bone healing based on bone density than the collagen membrane.